Recent developments in intelligent systems and interactive applications : proceedings of the International Conference on Intelligent and Interactive Systems and Applications (IISA2016) - Xhafa, Fatos; Patnaik, Srikanta; Yu, Zhengtao (Advances in intelligent systems and computing ;, 2017)
This book provides the latest research findings and developments in the field of interactive intelligent systems, addressing diverse areas such as autonomous systems, Internet and cloud computing, pattern recognition and vision systems, mobile computing and intelligent networking, and e-enabled systems. It gathers selected papers from the International Conference on Intelligent and Interactive Systems and Applications (IISA2016) held on June 25-26, 2016 in Shanghai, China. Interactive intelligent systems are among the most important multi-disciplinary research and development domains of artificial intelligence, human-computer interaction, machine learning and new Internet-based technologies. Accordingly, these systems embrace a considerable number of application areas such as autonomous systems, expert systems, mobile systems, recommender systems, knowledge-based and semantic web-based systems, virtual communication environments, and decision support systems, to name a few. To date, research on interactive intelligent systems has largely focused either on the realisation of the systems' capabilities or on the cognitive processes and/or behaviour of their users. With the rapid development of Internet-based technologies, the design of interactive intelligent systems is facing many emerging issues and challenges such as investigating the ways that artificial agents and human intelligence can collaborate for better performance, understanding user requirements and user cognitive processes, safeguarding user privacy, etc.